Hubungan Kebiasaan Screen Time dengan Perilaku Picky Eaters pada Anak Usia Pra-Sekolah - Lantip Widiantoko; Indra Tri Astuti; Herry Susanto (Journal of Health, Medical, and Psychological Studies, 2025)
This study examines the relationship between screen time habits and picky eating behavior among preschool-aged children. The increasing exposure of young children to digital devices has raised concerns regarding its impact on eating behavior, appetite regulation, and dietary patterns. Using a quantitative approach, this research analyzed screen time duration and picky eating behavior through structured questionnaires completed by parents of preschool children. Statistical analysis demonstrated a significant association between excessive screen time and the emergence of picky eating behavior, indicating that longer screen exposure tends to coincide with reduced food variety acceptance and irregular eating patterns. The findings also highlight the role of parental supervision and feeding practices in moderating the effects of screen time on children’s eating behavior. These results support existing evidence that prolonged screen exposure may interfere with hunger awareness and mealtime routines in early childhood. This study emphasizes the importance of regulating screen time and strengthening parental involvement to promote healthier eating behavior during the preschool period. The findings are expected to contribute to preventive strategies in child nutrition and early health education programs.